Molecular Catalysts for the Reductive Homocoupling of CO2 towards C2+ Compounds. Issue 19 (24th March 2022) - Liang, Hong‐Qing; Beweries, Torsten; Francke, Robert; Beller, Matthias
Abstract: The conversion of CO2 into multicarbon (C2+ ) compounds by reductive homocoupling offers the possibility to transform renewable energy into chemical energy carriers and thereby create "carbon‐neutral" fuels or other valuable products. Most available studies have employed heterogeneous metallic catalysts, but the use of molecular catalysts is still underexplored. However, several studies have already demonstrated the great potential of the molecular approach, namely, the possibility to gain a deep mechanistic understanding and a more precise control of the product selectivity. This Minireview summarizes recent progress in both the thermo‐ and electrochemical reductive homocoupling of CO2 toward C2+ products mediated by molecular catalysts. In addition, reductive CO homocoupling is discussed as a model for the further conversion of intermediates obtained from CO2 reduction, which may serve as a source of inspiration for developing novel molecular catalysts in the future. Abstract : This Minireview summarizes recent progress in molecular catalysis of CO2 and CO homocoupling through thermochemical and electrochemical reductive approaches. Particular attention is paid to C−C coupling processes that generate multicarbon products. The current challenges in this rapidly growing field are described and perspectives for possible future developments are outlined.